The Genus Jacaranda (Bignoniaceae): An Updated Review - Mostafa, Nada M; Eldahshan, Omayma A; Singab, Abdel Nasser B (Pharmacognosy Communications)
Genus Jacaranda has been traditionally used in treating skin disorders, venereal diseases, leishmaniasis, colds and rheumatism. Additionally, some species have shown diuretic and astringent properties. Objective: This review highlights and updates the traditional uses, pharmacology and phytochemistry of the genus Jacaranda. Materials and Methods: Information was obtained from Google Scholar, Scirus, PubMed and ScienceDirect. Results: Phytochemical studies on Jacaranda species have shown the presence flavonoids, phenylpropanoids, phenylethanoids, sterols and triterpenes. Extracts of different Jacaranda species possess a wide range of pharmacological activities, such as antioxidant antidepressant, antimicrobial, anticancer, anti-leishmanial, antiprotozoal, hypotensive and anti-hypertriglyceridemic activities. Conclusion: The genus Jacaranda is a natural source of antioxidants and has been widely used in traditional Ethnobotany. Thus, it could be exploited as a potential source for plant-based pharmaceutical products. The present review could form a sound basis for further investigation in the potential discovery of new natural bioactive compounds and could provide preliminary information for future research.
Keywords: Bignoniaceae; Genus Jacaranda; Pharmacology; Phytochemistry; Traditional uses